Three new spider species of Irura Peckham & Peckham, 1901 from China (Araneae: Salticidae) - Gan, Jia-Hui; Wang, Cheng; Peng, Xian-Jin (Zootaxa, 2017)
Three new species of the genus Irura are described from China: I. montiformis sp. nov., I. zhangae sp. nov. and I. yinae sp. nov. Distributional data, detailed morphological characteristics, and illustrations of body and genital organs are presented.